Towards Uniform Iodine Catalysis: Intramolecular C−H Amination of Arenes under Visible Light. Issue 29 (15th June 2016) - Martínez, Claudio; Bosnidou, Alexandra E.; Allmendinger, Simon; Muñiz, Kilian
Abstract: A photochemical catalytic amination of arenes is presented. The reaction proceeds under benign iodine catalysis in the presence of visible light as the initiator and provides access to a range of differently substituted arylamines. A total of 29 examples demonstrate the broad applicability of this mild oxidation method. The scope of the reaction could further be expanded to silyl‐tethered derivatives, which undergo intramolecular amination upon formation of seven‐membered heterocycles. Cleavage of the silicon tether provides access to the corresponding 3‐substituted anilines. Abstract : Iodine catalysis aminates arenes ! Iodine in catalyst loadings of 5–10 mol % provides access to intramolecular Csp 2 −N bond formation. Sulfonamides are employed as nitrogen sources, leading to excellent yields. In some cases, introduction of a traceless linker provides ready access to aniline derivatives.